Ayurvedic Management Of Vrikka Vikara (Ckd): A Case Study (Prakriti - The International Multidisciplinary Research Journal, 2025)
Chronic Kidney Disease (CKD) is a progressive disorder characterized by a gradual  decline in kidney function, often associated with risk factors such as hypertension,  diabetes, and cardiovascular diseases. Conventional treatments primarily focus  on delaying disease progression through pharmacological interventions and renal  replacement therapies. However, Ayurveda offers an alternative, holistic approach  targeting the underlying pathophysiology through Dosha balance and lifestyle  modifications. This case study evaluates the Ayurvedic management of a 32-year old male diagnosed with Grade III CKD at Jeena Sikho Lifecare Limited Clinic,  Kota, Rajasthan, India. The patient presented with lumbar pain, pedal edema,  and weakness. Diagnostic evaluations revealed a simple cortical cyst with cortical  echogenicity. After treatment, the patient exhibited significant symptomatic relief,  including reduced pedal edema and pain. Laboratory findings showed a decrease  in Blood urea levels from 129.8 mg/dL to 69 mg/dL and serum creatinine levels  from 8.46 mg/dL to 6.7 mg/dL. Additionally, there was a reduction in body weight  from 44 kg to 40 kg, reflecting improved overall health. The results suggest that  Ayurvedic therapies can enhance renal function and alleviate CKD symptoms,  providing a viable complementary approach to conventional treatments. The  findings highlight the potential of Ayurveda in CKD management by addressing  systemic imbalances through personalized interventions. Further research is  required to substantiate these observations and explore integrative treatment  models that combine Ayurvedic and modern medical approaches for optimal  patient outcomes.
Keywords: Chronic Kidney Disease (CKD); Ayurveda; Vataj pandu; Vrikka vikara; Renal Detoxification; Mutravaha Srotas Dushti